Ancient Indian perspectives and practices of mental well-being - Bhati, Ruchi; Mandal, Mitu; Singh, Tripti (Frontiers in Psychology, 2025)
In today’s fast-paced world, mental health issues are rising due to lifestyle changes, social media use, workplace burnout, and geopolitical events. Despite the urgent need to address the concern, mental health remains stigmatized, inaccessible, and undertreated. Contemporary mental health focuses more on symptoms rather than overall mental well-being. The holistic nature of ancient Indian mental health concepts and paradigms includes elements that contemporary mental health literature has overlooked. Indian texts like the Vedas, Upanishads, Bhagavad Gita, and Ayurveda make significant mention of mental health and provide applications of the psychological remedies to real-world circumstances. This study aims to explore and streamline the diverse practices and techniques buried in ancient Indian texts to offer evidence-based, real-world self-help techniques for overall mental well-being.